Twelve tips for surgeons to maximise medical student learning in the operating theatre. (4th March 2022) - Hunukumbure, Agra Dilshani; Leedham-Green, Kathleen E.; Rajamanoharan, Abirami; Patel, Kirtan; Tang, Alison; Das, Saroj
Abstract: Theatre-based learning is an essential component of undergraduate surgical education and offers a wide range of learning opportunities. However, studies have demonstrated that medical students have not always benefited from this holistic learning environment due to many reasons, including intimidation, hierarchies within the surgical environment and fear of making mistakes. The lead surgical educator's approach is an important influence on the experience and learning of their medical students. These twelve tips are aimed at surgical educators with undergraduate teaching responsibilities. This guidance is based upon evidence from literature and established theories of teaching and learning, supplemented by qualitative interviews with surgeons and medical students. The resulting tips were checked and refined by surgical teaching fellows. These learner-centred tips provide guidance on thorough induction, managing mutual expectations and approaches that optimise teaching and learning in the operating theatre. They are designed to support surgical educators in improving their students' engagement and learning experiences in this setting.